2023
DOI: 10.3390/children10050807
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Dental Emergencies during the COVID-19 Pandemic in Romania: A Retrospective Study

Abstract: Pediatric dental emergencies can occur as a result of untreated dental caries, or can be caused by trauma or periodontal issues. The lockdown imposed during the COVID-19 pandemic reduced the number of centers authorized to deliver dental services in Romania, with only a small number of dentists delivering dental emergency treatments. The aim of this study was to investigate the demographic characteristics of children and adolescent patients who were treated in the dental emergency department of Oradea, Romania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The most common treatments offered were extractions, pulpotomies, and fillings. These studies also revealed some of the challenges and barriers to providing pediatric emergency dental care during the pandemic, such as a lack of personal protective equipment (PPE), limited access to general anesthesia, delayed referrals, and parental fear of infection [ 26 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatments offered were extractions, pulpotomies, and fillings. These studies also revealed some of the challenges and barriers to providing pediatric emergency dental care during the pandemic, such as a lack of personal protective equipment (PPE), limited access to general anesthesia, delayed referrals, and parental fear of infection [ 26 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%